Head out swimming in water polo: a comparison with the front crawl in young female players - Zamparo, P.; Falco, S. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: In water polo, when swimming forward, players keep the elbows high (in order to stop opposing players from gaining possession of the ball) and this probably decreases the arm stroke efficiency ( p); moreover they keep their head out of the water (to see the rest of the pool and make the appropriate play) and this probably increases the trunk incline (TI) and the hydrodynamic resistance (Wd). Both factors, are expected to increase the energy demands of head out swimming (HOS) in comparison with front crawl swimming (FCS). METHODS: Two groups of young female water polo players (G-12, N = 11, 11.9 ± 1.4 years; 3.3 ± 0.5 years of practice and G-16, N = 10, 16.5 ± 1.3 years; 4.8 ± 0.6 years of practice) participated to the study, they were requested to swim with the two styles (HOS and FCS) at 4 self selected speeds (V, m . s-1: slow, moderate, fast and maximal) while their stroke frequency (SF, Hz), kick frequency (KF, Hz) and stroke length (SL, m) were assessed. The arm stroke efficiency ( p) was calculated according to the simple model proposed by Zamparo et al. (2005). During the experiments video records were taken in order to measure trunk incline (TI, degrees); the subjects were equipped with a waterproof heart rate monitoring system to record their heart rate (HR, bpm). RESULTS: The comparison between styles indicates that all parameters are significantly different in the two conditions (HOS and FCS). Swimming with the head out leads to a small (2%), albeit significant, reduction of the self select speed in comparison to FCS. During HOS the players have a larger (32%) TI and a higher HR (7%) compared to FCS. Moreover, in HOS, SL and p are significantly reduced (21% in both cases) whereas SF is increased (17%) in respect to FCS. Finally, KF is 10% lower during HOS than during FCS. DISCUSSION: HOS is characterized by relevant differences in the biomechanics of swimming in comparison with FCS. The need of keeping the head out of the water does indeed lead to an increase of TI whereas the need of keeping the elbows high does indeed lead to a reduction of p. Finally, both needs determine, as hypothesized, an increase of the energy requirement of this peculiar "form of locomotion in water" as confirmed, albeit indirectly, by the higher HR in HOS than in FCS at any given speed.